Parathyroid adenoma in a young female presenting with craniofacial brown tumor and acute pancreatitis – A case report - Chakravarti, Arunabha; Shukla, Indu; Mehra, Pravesh; Shukla, Shailaja (Indian Journal of Case Reports, 2019)
Solitary Parathyroid adenomas have a diverse clinical presentation. They may be asymptomatic or may sometimes lead to extensive bony resorption and replacement of bone by fibrous tissue, also known as a brown tumor. Brown tumor is a relatively rare presentation of primary hyperparathyroidism and is even rarer in a younger age group. Here, we report the case of a 20-year-old female presenting with craniofacial brown tumor and during the course of hospital stay; she also developed an attack of acute pancreatitis due to hyperparathyroidism. This case report emphasizes the importance of a complete investigative work up in patients presenting with maxillofacial bony lesions for early diagnosis and planning of definitive management.